Can Radiotherapy Be Omitted in Children With Hodgkin Lymphoma Who Achieve Metabolic Remission on Interim Positron Emission Tomography? Experience of a Tertiary Care Cancer Referral Center - Totadri, Sidharth (J Glob Oncol, 2017)
PURPOSE: Treating pediatric Hodgkin lymphoma (HL) involves a delicate balance between cure and reducing late toxicity. Fluorodeoxyglucose positron emission tomography (PET) combined with computed tomography (CT) identifies patients with early response to chemotherapy, for whom radiotherapy may be avoided. The role of PET-CT in upfront risk stratification and response–adapted treatment is evaluated in this study. METHODS: Patients with HL, who were younger than 18 years, were included. PET-CT was performed at baseline and after two cycles of chemotherapy. Patients were stratified into three risk groups: group 1 (stage I or II with no unfavorable features); group 2 (stage I or II with bulky disease/B symptoms); and group 3 (stage III/IV). A doxorubicin, bleomycin, vinblastine, dacarbazine–based regimen was used in early disease. A cyclophosphamide, vincristine, prednisolone, procarbazine, doxorubicin, bleomycin, vinblastine–based regimen was used in advanced disease. RESULTS: Forty-nine patients were included. Fifteen (31%), seven (14%), and 27 (55%) patients were included in groups 1, 2, and 3, respectively. Among 36 patients who underwent staging by PET-CT at diagnosis, seven (19%) patients were upstaged and one (3%) patient was downstaged by PET compared with CT. On the basis of negative interim PET responses, 39 (80%) patients were treated without radiotherapy. The 3-year event-free survival for the entire cohort was 91% (± 5.2%) and overall survival was 100%. CONCLUSION: PET-CT is an excellent stand-alone staging modality in HL. The omission of radiotherapy can be considered in patients who achieve metabolic remission on interim PET.